Effectiveness of Socioscientific Issues (SSI) Based Learning to Improve Argumentation Skills - Dewi, Anggita Intan Kumala; Suyono, Suyono; Erman, Erman (Jurnal Penelitian Pendidikan IPA, 2023)
The study aimed to examine the effectiveness of Socioscientific Issues (SSI) based learning to improve students’ argumentation skills (KArg) on additive materials. The learning tools had been developed using the ADDIE model comprising analysis, design, development, implementation, and evaluation. The learning tools were declared valid by expert judgments. There were 33 eighth-grade students at SMP Negeri 1 Pucanglaban, Tulungagung, Indonesia, chosen purposively as the research participants. The study used a one-group pretest-posttest research design to test the effectiveness of the learning tools. The students’ argumentation skills were measured using a rubric with a claim, evidence, and reasoning indicators. The obtained KArg scores before and after the implementation of the learning tools were analyzed using N-gain Score. The results showed that there was an increase in students’ KArg scores with the N-gain values on the three indicators of 0.87, 0.84, and 0.82 respectively, of which the scores were categorized in the high criteria. The increase in the three indicators showed the SSI-based learning tools on additive materials are effective in improving the junior high school students’ argumentation skills